Reflection on the Sacred Verse - Noraisah Nurul Fatwa, Mohd Razali (UMPSA, 2024)
In the Cave of Hira', silence reigns so near, Surah al-Alaq, melodious and clear, Divide words flow, a message sincere, For His beloved, a message to endear